Development of Problem-Based Learning Based on Google Sites Media in Indonesian Language Subject Class III at SD Muhammadiyah 4 Surabaya - Mustika, Pega; Putra, Deni Adi; Wahyuni, Holy Ichda (Widyagogik, 2025)
This study aimed to develop Google Sites-based learning media with a valid, practical, and effective Problem-Based Learning (PBL) approach in the Indonesian Language subject for grade III students at SD Muhammadiyah 4 Surabaya. This study uses the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The media developed includes interactive elements such as videos, quizzes, and educational games to increase students' interest and understanding. The data consisted of validity reviewed based on aspects of presentation, content, and language, practicality based on student responses after the media application, and effectiveness obtained from N-Gain pretest and posttest values. The study showed that PBL-based Google Sites were declared very valid, with an average validity of 95.83%. However, the practicality showed an acquisition of 94% with a quite practical category. Effectiveness showed an average N-Gain value of 0.90, including high category. This media was valid, advantageous, and effective in increasing interest and quality of Indonesian Language learning in grade III